2017
DOI: 10.2298/tsci140425002a
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computational fluid dynamics modeling of TiO2/R134a nanorefrigerant

Abstract: In this study, numerical investigations were carried out for R134a based TiO 2 nanorefrigerants. Forced laminar flow and heat transfer of nanorefrigerants in a horizontal smooth circular cross-sectioned duct were investigated under steady-state condition. The nanorefrigerants consist of TiO 2 nanoparticles suspended in R134a as a base fluid with four nanoparticle volume fractions of 0.0, 0.8, 2.0, and 4.0%. Numerical studies were performed under laminar flow conditions where Reynolds numbers range from 8•10 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The influences of heat loads and cooling capability of heat sink were considered. Numerical model has also been proposed based on FLUENT [16,18,19], to investigate the thermal hydrodynamic characteristics of the working fluid inside the TSVC. The results obtained in this paper could provide references on improving the thermal performance of this TSVC.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of heat loads and cooling capability of heat sink were considered. Numerical model has also been proposed based on FLUENT [16,18,19], to investigate the thermal hydrodynamic characteristics of the working fluid inside the TSVC. The results obtained in this paper could provide references on improving the thermal performance of this TSVC.…”
Section: Introductionmentioning
confidence: 99%
“…% CNT-R113 nanorefrigerant increase to 82%, 104%, 43% and 50%, respectively Tazarv et al [99] TiO 2 /R-141B Enhancement of convective heat transfer coefficient and higher vapour qualities 'nanorefrigerant' that can enhance refrigeration system performance. Several experimental and numerical investigations [56][57][58][59] have concluded that nanorefrigerants improve thermophysical properties, energy efficiency and the overall system performance. For instance, Fig.…”
Section: Nanorefrigerantsmentioning
confidence: 99%
“…Ahmed et al [22] conducted a numerical investigation for analysing the thermally radiative rotating flow of Maxwell nanofluid and concluded that the Brownian motion enhances the temperature field. Furthermore, few researchers have also conducted experimental and numerical studies on refrigerant based nanofluids (also known as nanorefrigerants) [23][24][25][26][27][28][29]. Helvaci and Khan [23] observed that the total entropy generation decreases with increase in Reynolds number in case of HFE 7000-based nanorefrigerants.…”
Section: Introductionmentioning
confidence: 99%